2012
DOI: 10.1097/00007890-201211271-00615
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery for Kidney Orthotopic Transplant in the Pig Model

Abstract: Background and Objectives: Laparoscopic surgery has rapidly expanded in surgical practice with well-accepted benefits of minimal incision, less analgesia, better cosmetics, and quick recovery. The surgical technique for kidney transplantation has remained unchanged since the first successful kidney transplant in the 1950s. Over the past decade, there were only a few case reports of kidney transplantation by laparoscopic or robotic surgery. Therefore, the aim of this study is to develop a laparoscopic technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…A large animal model previously was established to facilitate the training of surgeons to perform human laparoscopic kidney transplant. 15 The surgical time for laparoscopic kidney transplant may be longer initially than open 23 The ureteroneocystostomy was done laparoscopically using the same technique as the Lich Gregoir method. surgery but may be shorter in the future after the technique is improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large animal model previously was established to facilitate the training of surgeons to perform human laparoscopic kidney transplant. 15 The surgical time for laparoscopic kidney transplant may be longer initially than open 23 The ureteroneocystostomy was done laparoscopically using the same technique as the Lich Gregoir method. surgery but may be shorter in the future after the technique is improved.…”
Section: Discussionmentioning
confidence: 99%
“…A live animal (pig) model of laparoscopic kidney transplant has been described with orthotopic autotransplant. 15 In the pig model, the renal artery is anastomosed to the stump of the renal artery, the renal vein is anastomosed to the end of the renal vein stump, and the ureter is anastomosed to the ureter in an end-to-end fashion. Although the porcine renal artery is small (diameter, 2 to 3 mm), the frequency of successful vessel anastomosis is 70%, and a reliable and safe vessel anastomosis was confirmed with a laparotomy at the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…First, the surgical technique was established on a large animal pig model. It was demonstrated that laparoscopic kidney transplant was feasible and safe and that immediate renal function can be achieved (8)(9)(10). Following the experiment, a human cavader model was established for laparoscopic kidney transplant by using extra-peritoneal approach (11).…”
Section: Methodsmentioning
confidence: 99%
“…In their study of laparoscopic orthotopic kidney transplant, Be and associates used a similar method through a 5-mm trocar. 10 However, Modi and associates did not maintain cold ischemia. Recently, a study following the IDEAL (Idea, Development, Exploration, Assessment, Long-term follow-up) model for the assessment of new surgical procedures was published in which robotic kidney transplant with regional hypothermia was studied.…”
Section: Figure 3 Time Required To Perform the Transplant In Each Casementioning
confidence: 99%